PERAN TEKNOLOGI DALAM PENGELOLAAN PENDIDIKAN INKLUSIF - Setyawati; Madjdi, Ahmad Hilal; Hariyadi, Ahmad (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2025)
This study aims to examine the role of technology in optimizing inclusive education management at the Jepara State Special School (SLB), particularly through adaptive learning applications, digital assistive devices, and communication platforms. Using a qualitative approach, this study describes the contribution of technology to the effectiveness of learning management and responsive decision-making. The research findings indicate that technology supports flexible and real-time learning processes; however, its implementation still faces challenges related to infrastructure, teachers' limited digital literacy, and access disparities in certain areas. Therefore, policies ensuring equitable access, ongoing training for educators, and the development of adaptive curricula are necessary. Optimizing the role of technology in inclusive education at Jepara State SLBs can create a more equitable and efficient learning environment and help achieve the goal of providing education for all.